Exercise haemodynamics after restrictive mitral annuloplasty for functional mitral regurgitation. (25th May 2019) - Petrus, Annelieke H J; Tops, Laurens F; Holman, Eduard R; Marsan, Nina A; Bax, Jeroen J; Schalij, Martin J; Steendijk, Paul; Klautz, Robert J M; Braun, Jerry
Abstract: Aims: Restrictive mitral annuloplasty (RMA) can provide a durable solution for functional mitral regurgitation (MR), but might result in obstruction to antegrade mitral flow. Aim of this study was to assess the magnitude of change in mitral valve area (MVA) during exercise after RMA, to relate the change in MVA to left ventricular (LV) geometry and function, and to assess its haemodynamic and clinical impact. Methods and results: Bicycle exercise echocardiography was performed in 32 patients after RMA. Echocardiographic data at rest and during exercise were compared with preoperative echocardiographic data. Clinical endpoints were collected following the study visit. MVA increased during exercise in 25 patients (1.6 ± 0.4 cm 2 to 2.0 ± 0.6 cm 2, P  < 0.001), whereas MVA decreased in 7 patients (1.8 ± 0.5 cm 2 to 1.5 ± 0.4 cm 2, P  = 0.020). Patients with an increased MVA showed a significant reduction in LV volumes at rest compared to preoperatively, and an increase in stroke volume and cardiac output (CO) during exercise. In patients with decreased MVA, LV reverse remodelling was absent and myocardial flow reserve limited. Patients with decreased exercise MVA had a higher increase in mean pulmonary artery pressure (PAP) with respect to CO and worse survival 36 months after the study visit (69±19% vs. 92±5%, P  = 0.005). Conclusions: Both increased and decreased MVA were observed during exercise echocardiography after RMA for functional MR. Change in MVA was related to the extent of LV geometrical and functional changes. A decreased MVA during exercise was associated with a higher increase in mean PAP with respect to CO, and worse survival.